Saving the Planet: A Guide for Organisations to Formulate a Green Policy - Blair, Garry; Woodcock, Helen (Apex Journal of Business and Management, 2024)
Organisations are now required to consider their impact on the environment, rather than focus entirely on their own objectives for profit generation and service delivery. An effective environmental or 'green' policy is, thus, essential. This necessitates an external rather than internal perspective. There is recognition by organisations that public image will be affected by such policies and their operation in practice. This article addresses the key facets of such policies, to assist organisations in their construction. The need to set goals that are aligned with the business objectives, create an appropriate culture as well as programmes, such as on transport and recycling, is paramount. Educating the staff and effective communication should be prioritised, in order to implement this policy. External aspects should be addressed, utilising effective change management. These projects and measures should be properly resourced. The focus should be on customers and suppliers, to ensure that such 'green' policies are effective. Organisations should be prepared to exclude parties who do not align with these policies from their operations, as far as possible. The director of an  international company in the 'green' energy sector was interviewed. A selection of the principal journals was surveyed to select key  articles on this theme. The data was then analysed and the main themes extracted for this exploratory research.